Attitudes is the most important environmental factor for use of powered mobility devices - users' perspectives - Widehammar, Cathrine; Lidström Holmqvist, Kajsa; Pettersson, Ingvor; Hermansson, Liselotte Norling (Scandinavian journal of occupational therapy, 2020)
Introduction: Different factors in the environment influence the use of powered wheelchairs or powered scooters, i.e. powered mobility devices (PMDs), but there is limited knowledge about how these factors interact and if any factor has a greater impact. According to the ICF the environment consists of five areas. Aim: To describe users' experiences of how environmental factors from all ICF areas influence the use of PMDs. Methods: Descriptive qualitative design including 14 interviews with PMD users, analyzed using inductive qualitative content analysis. Findings: Use of PMDs means a conditional freedom depending on the interaction of several environmental factors. Regardless of environmental factor the societal attitudes were always present, directly or indirectly, and influenced the participants' feeling of being included and involved in society. The environmental factors and how they influence PMD use are described in four categories, comprising the following subjects: societal attitudes, the service delivery process, accessibility to the physical environment and financial resources. Conclusion: The findings show that societal attitudes influence all other factors, directly by others people's attitudes, or indirectly by how legislation and guidelines are formulated, interpreted and applied. Therefore, a change of societal attitudes seems necessary to increase accessibility and participation for PMD users.